Ewing Sarcoma/Peripheral Primitive Neuroectodermal Tumor in the Adrenal Gland of a Child (Iranian Journal of Kidney Diseases, 2018)
Ewing sarcoma/peripheral primitive neuroectodermal tumor (ES/PNET) typically occurs in long or flat bones, soft tissues, or less often, solid organs. Ewing sarcoma/peripheral primitive neuroectodermal tumor arising from the adrenal gland is extremely rare, especially in children, and only limited cases are reported previously. Herein, we review a case of a 22-month-old girl who presented to our department with abdominal pain, bulging of the left flank, and a nonfunctioning adrenal lesion which was found to be an adrenal ES/PNET. The patient was successfully treated with surgery and adjuvant chemotherapy. Since delayed diagnosis may result in metastatic lesions, this case underscores the importance of considering ES/PNET in the differential diagnosis of large adrenal masses.